2007
DOI: 10.1103/physrevlett.98.125001
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-Electrodynamical Photon Splitting in Magnetized Nonlinear Pair Plasmas

Abstract: We present for the first time the nonlinear dynamics of quantum electrodynamic (QED) photon splitting in a strongly magnetized electron-positron (pair) plasma. By using a QED corrected Maxwell equation, we derive a set of equations that exhibit nonlinear couplings between electromagnetic (EM) waves due to nonlinear plasma currents and QED polarization and magnetization effects. Numerical analyses of our coupled nonlinear EM wave equations reveal the possibility of a more efficient decay channel, as well as new… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 34 publications
0
39
0
Order By: Relevance
“…Moreover, it has recently been experimentally shown that quantum dispersive effects are important in inertial confinement plasmas [106]. The list of quantum mechanical effects that can be included in a fluid picture includes the dispersive particle properties accounted for by the Bohm potential [83,84,85,86,87,88,89,90,91,92,93,94], the zero temperature Fermi pressure [83,84,85,86,87], spin properties [95,96,97], certain quantum electrodynamical effects [45,46,59,107], nano-plasmonics devices [108], as well as quantum effects in the classical regime [109,110]. Within such descriptions, [46,59,83,84,85,86,87,95,96,107] a unified picture of quantum and classical collective effects can be obtained.…”
Section: Quantum Plasmasmentioning
confidence: 99%
“…Moreover, it has recently been experimentally shown that quantum dispersive effects are important in inertial confinement plasmas [106]. The list of quantum mechanical effects that can be included in a fluid picture includes the dispersive particle properties accounted for by the Bohm potential [83,84,85,86,87,88,89,90,91,92,93,94], the zero temperature Fermi pressure [83,84,85,86,87], spin properties [95,96,97], certain quantum electrodynamical effects [45,46,59,107], nano-plasmonics devices [108], as well as quantum effects in the classical regime [109,110]. Within such descriptions, [46,59,83,84,85,86,87,95,96,107] a unified picture of quantum and classical collective effects can be obtained.…”
Section: Quantum Plasmasmentioning
confidence: 99%
“…Recently the matterless double slit was suggested to observe the photon-photon scattering and to realize the controlling of light with light [3,4]. The QED corrections can give rise to single photon effects, such as vacuum birefringence [5], photon splitting [6], and lensing effect in strong magnetic fields, as well as collective nonlinear excitations, such as self-focusing of photons, the formation of solitons, generation of harmonic waves, etc. The photon acceleration associated with collective photon interactions has been explored by considering a test photon immersed in a modulated radiation background [7].…”
Section: Introductionmentioning
confidence: 99%
“…[15,16,17,18]. Moreover, studies taking both certain quantum electrodynamical effects, such as photon splitting, as well as collective particle effects have been made [37,38].…”
Section: Introductionmentioning
confidence: 99%